Vasoconstrictor and coagulation activator entrapped chitosan based composite hydrogel for rapid bleeding control. (15th April 2021) - Sundaram, M. Nivedhitha; Mony, Ullas; Varma, Praveen Kerala; Rangasamy, Jayakumar
Graphical abstract: Highlights: PA and Ca entrapped Cs hydrogel (Cs-PA-Ca) was prepared and characterized. Cs-PA-Ca hydrogel was injectable, adhesive and found to be cyto and hemocompatible. Cs-PA-Ca hydrogel causes RBC/platelet aggregation and also activates coagulation. Cs-PA-Ca hydrogel has ability to act on all mechanisms involved in hemostasis. Cs-PA-Ca hydrogel showed rapid control of oozing and pressured bleeding conditions. Abstract: Chitosan (Cs) as a hemostatic agent has been in use to control hemorrage. Composite hydrogel formed by entrapment of vasoconstrictor-potassium aluminium sulfate (0.25 %PA) and coagulation activator-calcium chloride (0.25 %Ca) into Cs (2 %) hydrogel would enhance the hemostatic property of Cs. In this work, the prepared composite hydrogel was injectable, shear thinning, cyto and hemocompatible. The 2 %Cs-0.25 %PA-0.25 %Ca composite hydrogel caused rapid blood clotting by accelerating RBC/platelet aggregation and activation of the coagulation cascade. Further, in vivo studies on rat liver and femoral artery hemorrage model showed the efficiency of 2 %Cs-0.25 %PA-0.25 %Ca composite hydrogel to achieve hemostasis in a shorter time (20 ± 10 s, 105 ± 31 s) than commercial hemostatic agents-Fibrin sealant (77 ± 26 s, 204 ± 58 s) and Floseal (76 ± 15 s, 218 ± 46 s). In in vivo toxicological study, composite hydrogel showed material retention even after 8 weeks post-surgery, therefore excess hydrogel should be irrigated from site of application. This prepared composite hydrogel based hemostatic agent has potential application in low pressure bleeding sites.